HIGHER EDUCATION AND ENGLISH AS AN INTERNATIONAL LINK LANGUAGE - Chandrakar, Durga (ShodhKosh: Journal of Visual and Performing Arts, 2024)
English is the dominant language in the United Kingdom, the United States many Commonwealth nations including Australia and Canada, and other former British colonies. It is also a dominant or official language in many countries formerly under British rule. English is now the fourth (or possibly third depending on the source) most widely spoken native language worldwide (after Chinese, Hindi and debatably Spanish), with some 380 million speakers. English is also the dominant member of the Germanic languages. It has lingua franca status in many parts of the world, due to the military economic, scientific, political and cultural influence of the British Empire in the 18th, 19th and early 20th centuries and that of the United States from the early 20th century to the present. Through the global influence of native English speakers in cinema, airlines, broadcasting, science, and the Internet in recent decades, English is now the most widely learned second language in the world although other languages such as French and Spanish also retain much importance worldwide. Many students worldwide are required to learn at least some English, and a working knowledge of English is required in many fields and occupations.